2016
DOI: 10.1155/2016/2916027
|View full text |Cite
|
Sign up to set email alerts
|

Frosted Branch Angiitis Secondary to Familial Mediterranean Fever Resembling Central Retinal Vein Occlusion

Abstract: Purpose. To report a case of unilateral frosted branch angiitis (FBA) resembling central retinal vein occlusion associated with Familial Mediterranean Fever (FMF). Case Report. A 32-year-old woman presented with progressive, painless vision loss in her left eye lasting for 2 days. She was clinically diagnosed with FMF 2 months ago. The best-corrected visual acuity (BCVA) was 20/20 in her right eye and there was light perception in the left. Ophthalmologic examination revealed severe retinal vasculitis showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Unclassified vasculitis was described in a total of 11 FMF patients from various case reports (74–80, 84–87). FMF was associated with unclassified medium vessel vasculitis in three patients (patient 1, 2, 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unclassified vasculitis was described in a total of 11 FMF patients from various case reports (74–80, 84–87). FMF was associated with unclassified medium vessel vasculitis in three patients (patient 1, 2, 3).…”
Section: Resultsmentioning
confidence: 99%
“…The co-occurrence of FMF and unclassified small vessel vasculitis was described in seven patients (patients 4, 5, 6, 7, 12, 13, and 14) (77–80, 8587). Vasculitis phenotypes were heterogeneous.…”
Section: Resultsmentioning
confidence: 99%
“…Substantial overlap between pathogenic mechanisms of both diseases seems possible. [11,13,14,28]. However, although the role of several in ammasomes has been discovered in the pathogenesis of several OIDs, the pyrin in ammasome has not been shown to be involved in any OIDs to date [29].…”
Section: Discussionmentioning
confidence: 99%
“…The association of FMF with other in ammatory diseases such as spondyloarthritis, immunoglobulin A vasculitis/Henoch-Schönlein purpura, polyarteritis nodosa, in ammatory bowel disease (IBD), chronic arthritis, and protracted febrile myalgia has been well de ned and it is suggested that FMF and associated in ammatory diseases should not be considered as the coexistence of different clinical entities [5][6][7][8]. Previous studies have reported uveitis, scleritis, episcleritis, optic neuritis, and frosted branch angiitis of retinal vein among ocular in ammatory manifestations of FMF [9][10][11][12][13][14]. Although FMF has been thought of as a predisposition to a variety of in ammatory processes, the possible association of FMF with ocular in ammatory diseases (OIDs) is not clear contrary to its known association with sacroiliitis, vasculitis, and IBD.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of underlying causes has important implications for therapy. Reported conditions that can present with secondary FBA include herpes simplex virus retinitis, varicella zoster virus retinitis, cytomegalovirus retinitis, toxoplasmosis, tuberculosis, familial Mediterranean fever, antiphospholipid antibody syndrome, systemic lupus erythematosus, syphilis, HIV infection, Behçet's disease, Hodgkin lymphoma (HL), and direct ocular invasion by malignant cells …”
Section: Introductionmentioning
confidence: 99%